Construction of Generation Z's Monotheism on Social Media: A Phenomenological Study of UIN Palu Students - Nursyam Nursyam; Kamridah Kamridah; Rusli Takunas; Naimah; Makmur Harun (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
Digital transformation fundamentally altered how Generation Z constructs aqidah (theology), making social media the primary religious information source and challenging traditional authorities. This study is vital because theological fragmentation risks superficiality and cognitive dissonance among future religious educators. Prior research neglected the specific phenomenological process of tauhid (monotheism) construction by Gen Z. Utilizing Husserl’s transcendental phenomenology, this qualitative study explored the